Tacit knowledge sharing to improve teachersâ€™ performance - Triana Triana; Rugaiyah Rugaiyah (Jurnal Akuntabilitas Manajemen Pendidikan, 2023)
In the current industrial revolution 4.0 era, teachers are required to constantly develop themselves and improve their performance. This is because teachers are the frontliners who directly interact with students. Teachers are one of the spearheads in educational institutions that determine student success. Teachers who are of superior quality will certainly give their best performance. Therefore, this study aims to analyze how teachers are able to exploit the knowledge and skills that exist in themselves by optimizing all sources of knowledge around them through knowledge sharing activities among teachers, particularly tacit knowledge sharing so that they can improve their performance.Â  The methodology used in this research is a systematic approach with the Systematic Literature Review method with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analysis) model from articles published from 2012 to 2022. Based on the results of these studies, it is learnt that knowledge sharing activities among teachers will encourage individual knowledge improvement and produce new knowledge as a process of exchanging knowledge both implied and explicit from each individual.